Teaching design concept and its importanceParticipants in the design of the teaching - Venus Ali Maytham; Zeina Abdel Amir Hassan (Genius Journals, 2022)
Intentional and unintended educational processes vary, but teaching is concerned with prior planning. Talking about it requires a logical and organized approach to the processes of designing teaching, implementing and evaluating the educational process, in order to achieve the goals and objectives. It focuses on the amount of knowledge that should be provided to the learner recently. As for the recent development of educational psychology and its theories, teaching design appeared, which It requires the teacher to pay attention to some considerations about how to present the lesson and organize knowledge based on the learners’ experiences, needs and abilities. The science of design, with its originality and modernity, plays an active and influential role in upgrading the educational process and increases the probability of the teacher’s success in achieving his goals and makes him able to give and manage the classroom effectively and efficiently.
Keywords: logical; designing teaching; organize knowledge.